Strategy Marketing Product in Increase Consumer Interaction on Social Media - Rahmi, Nazhilatur; Soraya Lestari (International Journal of Economics and Management Research, 2025)
Product Marketing Strategy in Increasing Consumer Interaction on Social Media. Social media is a platform that is widely used by the public. Its existence has great potential for businesses to get closer to customers, increase profits, strengthen marketing and communication strategies, and improve cost efficiency and effectiveness. This research aims to explore the marketing strategy and understand the important role social media plays when marketing the products needed. The research used several interviews and employed qualitative methods. Qualitative research is typically used to answer broad questions, but it can also be applied to explore more focused questions in accordance with the research objectives. The object of the social media marketing interview was obtained based on the results of the interview with the seller or owner of the online shop. The results obtained from the interview on Marketing Strategy Based on Social Media are as follows: determining the right platform (the selected platform should align with the product and target audience, such as Facebook and Tiktok), marketing through video, consistent and quality content, and determining target consumers